Analysing the Role of Money Supply on Inflation: A case Study of Pakistan - Gola , Asghar Ali; Qamri, Ghulam Muhammad; Panhyar, Abdullah; Khan, Qasim Raza; Ali, Imran (iRASD Journal of Economics, 2023)
Monetary tools, money supply, and exchange rates play a significant role in a country's growth and substantially impact its development trajectory. In order to address this issue, the study empirically examines the relationship between money supply, exchange rate, and Inflation in Pakistan. The study utilized annual time series data from 1990-2020 from the State Bank of Pakistan (SBP) and World Development Indicators (WDI). To avoid spurious results, the Phillips-Perron unit root test and the Augmented Dickey-Fuller test were applied to check the data stationarity, which was integrated at different orders of integration. The exchange rate and inflation are stationary at the 1st difference I(1), while the money supply is stationary at the same level I(0). The Autoregressive Distributed Lag (ARDL) model analyzes the variables' short- and long-term relationships. The study confirms the presence of both short-run and long-run relationships among the variables. The results show that money supply and exchange rates significantly impact inflation positively. A negative and significant error correction term (ECT) indicates strong equilibrium convergence among variables. The upper and lower bounds values are below the F-statistics, indicating a significant long-term association between the statistically significant variables. The research contributes to current knowledge by presenting new awareness into the dynamic relations among money supply, exchange rate, and inflation. Furthermore, this study will help to design monetary policy to achieve specific targets to control inflation and volatility in exchange rates. It will help regulators and policymakers stabilize financial markets and the supply and demand of products, prevent pricing mechanisms and import exports, and increase the balance of payment accounts.